(untitled) (Географический вестник=Geographical bulletin, 2017)
Рассмотрено воздействие антропогенного фактора на природную среду. На примере р. Риони, крупнейшей реки Западной Грузии, показано, как человеческий фактор влияет на естественный режим реки, изменение которого приводит к последствиям, требующим огромных капитальных вложений. Так, обвалование русла реки повысило расходы воды на 9% в результате пойменной аккумуляции, что поставило г. Поти под угрозу затопления. В статье показано, что без всестороннего учета последствий вмешательства в природную среду проекты обречены на неудачу. ANTHROPOGENIC INFLUENCE ON THE NATURAL PROCESS OF RIONI RIVER NEAR THE TOWN OF POTI Influence of the anthropogenic factor on an environment is considered in article. It is shown on an example of Rioni river which is the largest river of the Western Georgia. Human factor influences a natural mode of the river which consequences manage greater capital expenses. So сreation of protective dams channels of the river have raised charges of water on 9 % due to inundated accumulation therefore Poti has appeared under threat of flooding. It was necessary to throw a part of a drain of water in a new channel owing to what deficiency of deposits has caused washout of delta of an old channel and approach of sea water to the built up parts of city. In article it is evidently visible, that without the account of factors of consequences all projects are doomed to failure.